Transfer of knowledge in knowledge management systems : unexplored issues and suggested studies - Huber, G.P. (2001)
Identifies some major problems associated with knowledge transfer, and articulates some of the most important issues associated with these problems. Raises eight research questions that, if answered with sound studies, would enable organisations to be more effective in their transfer of knowledge.